Implementation of DMAIC Framework to Reduce Defects in Spray Painting Process - Sarah Ayu Aqila; Nur Budi Mulyono (Jurnal Impresi Indonesia, 2025)
The spray painting process at PT Tritek Indonesia plays a vital role in determining final product quality, especially for components used in the automotive and electronics industries. However, recurring defects such as NG total and under paint have led to elevated production losses and pose risks to customer satisfaction and process stability. This research aims to identify the root causes of these defects and propose structured improvements using the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) methodology. During the Measure phase, data from January to March 2025 indicated that defect rates remained high, with DPMO values of 116,160 (? = 1.19), 89,553 (? = 1.34), and 110,861 (? = 1.22) respectively, highlighting low process capability and the need for urgent improvement. Root cause analysis using Fishbone Diagrams and FMEA identified several key contributors to the high defect rate, including the lack of operator discipline in pretreatment and thickness inspection, inconsistent spraying techniques, suboptimal spray gun performance due to nozzle wear, and dusty spray booth conditions. To address these root causes, the proposed solutions in the Improve phase include implementing a daily pretreatment checklist, structured coating thickness inspections with periodic training and microbreaks, development of a spray painting assistive tool to standardize distance and angle, a preventive maintenance schedule for spray gun components, and the implementation of 5S principles to improve cleanliness in the painting area. The Control phase proposes regular audits, performance documentation, and bi-weekly evaluation meetings to ensure long-term compliance. This research provides practical insights for small-to-medium manufacturing enterprises in Indonesia to initiate structured quality control programs and gradually advance towards higher process capability and reduced defect variability.